Foreword: Civilian Involvement in Peacekeeping Operations in the Western Balkans - Woodhouse, Tom (Journal of Regional Security, 2018)
Peacekeeping has come a long way since the basic principles which define it were laid down by Lester Pearson and Dag Hammarskjold, to guide the deployment of the first full UN mission, UNEF I, in 1956. Since 1956, it has been generally accepted that peacekeeping is a function of the UN, but there are occasions when it has been used by international and regional organisations other than the UN, and there are operations which can be seen as early uses of peacekeeping which predated the formation of the UN in 1945. After the First World War, for example, multinational military bodies were used to establish and administer the new frontiers of Europe agreed by peace treaties after the war. Also after the First World War the League of Nations conducted activities which were comparable in some respects to peacekeeping. However, since 1945 peacekeeping has been the technique most frequently used by and associated with the United Nations to terminate conflicts and establish peace, so much so that the organisation was awarded the Nobel Peace Prize for its peacekeeping activities in 1988 and indeed Pearson and Hammarskjold, the two people who ‘invented’ peacekeeping as a so-called chapter six and a half activity of the UN were also awarded the Nobel Peace Prize in 1957.